Early symptoms and 12-week follow-up of pediatric omicron infections during the Beijing outbreak - Qin Hui; Jing Liu; Hua Fan; Xiaonan Hou; Xuan Li; Wei Li; Qi Zhang (Frontiers in Pediatrics)
ObjectivesTo investigate the epidemiological and clinical characteristics of children infected with the Omicron variant of SARS-CoV-2 during the early outbreak in Beijing, with particular attention to symptom profiles, clinical management, and persistent symptoms at 12 weeks post-infection.MethodsThis prospective study enrolled children under 18 years of age with confirmed or suspected Omicron infection in Beijing between December 2022 and January 2023. Data were collected via an online questionnaire targeting both community-managed and outpatient children. A follow-up survey was conducted at 12 weeks post-infection to assess long-term symptoms.ResultsA total of 1,610 children aged 15 days to 18 years were included (median age: 3.00 years; 51.4% boys). Fever (96.4%) was the most common symptom, with a mean peak temperature of 39°C (range: 37.6–41°C). Other frequent symptoms included cough (59.1%), runny nose (43.7%), and fatigue (22.1%). The mean duration of fever was 2.05 ± 1.09 days, and the mean duration of all symptoms was 5.89 ± 4.35 days, with both showing significant differences across age groups (p < 0.001). By one week post-infection, symptoms had resolved in 34.2% of cases. At 12 weeks, 2.9% (43/1,471) of children still reported persistent symptoms. The most common were cough (1.4%), nasal congestion (1.1%), dry throat and exertional dyspnea (each 0.7%), and fatigue (0.6%).ConclusionsOmicron infection affected children across all age groups, with a higher prevalence in younger children. Fever and cough were the predominant acute symptoms, while a small subset reported mild persistent symptoms 12 weeks post-infection.